Mononuclear palladium(ii) and platinum(ii) complexes of P, C-donor ligands: synthesis, crystal structures, cytotoxicity, and mechanistic studies of a highly stereoselective Mizoroki–Heck reaction. Issue 12 (6th November 2017) - Sabounchei, Seyyed Javad; Hosseinzadeh, Marjan; Salehzadeh, Sadegh; Maleki, Farahnaz; Gable, Robert W.
Abstract : Pallada- and platinacycle complexes exhibit potential orientations in stereoselective transformations and anticancer metallodrugs. Abstract : Cyclometalated Pd(ii ) and Pt(ii ) complexes of unsymmetrical phosphonium ylides Ph2 P(CH2 ) n PPh2 C(H)C(O)C6 H4 R (R = Ph, n = 2 (Y 1 ); R = NO2, n = 1 (Y 2 )) have been prepared through a simple procedure to explore new directions in stereoselective catalysis and antitumor metallodrugs. The new pallada- and platinacycle complexes have been characterized by spectroscopic, crystallographic, and density functional theory methods. Catalytic activity and in vitro cytotoxicity of these compounds, as assessed, respectively, using the Mizoroki–Heck reaction and a human tumor cell line, have been evaluated. In particular, a mechanistic pathway of the Heck reaction catalyzed by Pd(ii ) complex (1 ) with a chelating P, C- ligand has been investigated by DFT studies. The computational results were in agreement with those of experiments, which demonstrate the high stereoselectivity in the Pd-catalyzed Csp 2 –Csp 2 cross coupling reaction and the origin of an observed coordination mode in the prepared complexes. In this article, the cytotoxicity effects of four-coordinated Pt(ii ) complex (2 ) against MCF-7 cells clearly reveal its great potential as an antitumor agent.